2017
DOI: 10.1093/jisesa/iex050
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Male Drosophila melanogaster Exposed to Ethylparaben Using Digital Gene Expression Profiling

Abstract: Ethylparaben (EP) has been shown to have estrogenic effects and can affect the normal development, longevity, and reproductive system of some animals. In this study, we investigated the effects of EP in male Drosophila melanogaster using transcriptome analysis or digital gene expression profiling. We then screened differentially expressed genes (DEGs) between the two groups (EP-treated and control group) of Drosophila, and performed clustering analysis, gene ontology (GO) function annotation, kyoto encyclopedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 72 publications
(78 reference statements)
1
2
0
Order By: Relevance
“…Based on annotation, we identified 46 putative OBP genes, 22 CSPs, 38 ORs, 13 IRs, 6 SNMPs, and 5 GRs in T. meditationis ( Figure 3 a). There were more genes in OBP and OR than in GR and SNMP, consistent with the sizes of these gene families in most insects [ 7 , 26 ]. The ENC and GC12/GC3 values of the six gene families in T. meditationis were further compared with those of the whole gene sequence, and the results showed that the codon bias of the chemosensory genes did not differ from the codon bias of the whole genome ( Figure 3 b).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Based on annotation, we identified 46 putative OBP genes, 22 CSPs, 38 ORs, 13 IRs, 6 SNMPs, and 5 GRs in T. meditationis ( Figure 3 a). There were more genes in OBP and OR than in GR and SNMP, consistent with the sizes of these gene families in most insects [ 7 , 26 ]. The ENC and GC12/GC3 values of the six gene families in T. meditationis were further compared with those of the whole gene sequence, and the results showed that the codon bias of the chemosensory genes did not differ from the codon bias of the whole genome ( Figure 3 b).…”
Section: Resultssupporting
confidence: 56%
“…Transcriptomic analysis can reveal an organism’s expressed gene sequences, annotations, and expression levels [ 5 , 6 ]. For research that is less concerned with other genomic factors (e.g., repetitive elements), the transcriptome provides sufficient data for probing functional components of a given organism’s genome [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…DGE technology has been used more commonly in examining the differences of transcriptional responses in different tissues and organs. This is because DGE can identify millions of differentially expressed genes before prior annotation and the organisms without much genetic information are also allowed to be analyzed by DGE [ 14 ].…”
Section: Introductionmentioning
confidence: 99%